Pembuatan Brem Padat dari Umbi Porang - Purwanto, Agus (Widya Warta, 2014)
Bulbs of great varieties can be used as raw materials for alcoholic fermentation. The purpose of this experiment is to study the effect of different time of alcoholic fermentation on the quality of solid brem produced. This research was conducted by using completely randomized design with three replications. The samples comprised 4 treatments of fermentation time, including 2 (two) days, four (4) days, six (6 ) days and 8 ( eight ) days. The solid brem quality was determined by measuring the alcohol content, yield, pH and moisture content. The results showed that all four treatments of fermentation affected the quality of the solid brem, which includes analysis of alcohol content, solid brem yield, and pH. While, the results of analysis of the water content measurements showed no significant difference. The results of fermentation with longer time showed an increase in alcohol content and yield, while the level of acidity ( pH ) decreased.